Risk factors for atopic dermatitis in southern Puerto Rico - Montealegre, Federico; Villa, Jaime; Vargas, Wanda; Hart, Barbara; Bayona, Manuel (Puerto Rico Health Sciences Journal, 2009)
Background: Little is known about the risk factors and exposures to aeroallergens in subjects with atopic dermatitis (AD) in Southern Puerto Rico. The objective was to determine the prevalence of skin reactions to aeroallergens and to analyze self-reported risk factors in AD patients and a nonallergic control population. Methods: A cross-sectional study was conducted which included 726 AD patients and 313 nonallergic control subjects. Skin tests were conducted and a questionnaire was self-applied to all participants. Results: Seventy six percent of the AD patients showed at least one positive skin reactions to aeroallergens. Of these, half had positive skin reactions to dust mites, and one third to Periplaneta americana. A low prevalence of positive skin reactions to dog, cat, plant and fungal allergens was detected. Co-sensitivitity between mites and cockroaches was 30%. The maximum skin reactivity to mites was at 10-19 years of age declining thereafter while skin reactivity to dogs, and plants increased with age. No significant differences in the prevalence of skin reactions was observed between the male and female AD population. Conclusions. Of the aeroallergens tested, those derived from dust mites are the most frequent sensitizing agents in the AD patients. Data also showed that the mites B. tropicalis and E. maynei are also important sources of sensitization. Our study show that young patients specially those between the age of 10-19 age group are the most allergic. Being female, or having an asthmatic father are significant risk factors associated with allergen sensitivity in the AD population.